Sifat-Kepribadian dan Dukungan Organisasi Sebagai Prediktor Komitmen Organisasi Guru Pria di Sekolah Dasar - Hutapea, Bonar (UI Scholars Hub, 2012)
Unlike in business and industrial setting, researches examining organizational commitment in academic/educational realm have been scarce. In particular, because of significant role of male teacher in students’ psychological development, it is necessary to reveal male teachers’ commitment due to persistent huge disparity of their numbers as compared with their female counterparts. The purpose of this study was to investigate the predictability of traits-personality and perceived organizational support towards male teachers’ organizational commitment and also to examine the relation of five factors of personality with dimensions of their commitment. Participants for this study consisted of male teachers of private elementary schools in Jakarta. This study found that traits-personality and perceived organizational support made significant contributions to teachers’ commitment. More over, it was determined that two of five factors of personality were predictors for male teachers’ commitment dimensions. Limitations and implications of this study are discussed.